Round Table on "Leveraging ICT to Accelerate Indian Agriculture" - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
A roundtable was held in January 2019, as a beginning to a project on the use of ICTs in Agriculture to spur innovation and growth for Indian small farmers. This paper summarises the discussions and lists the important aspects which were identified through the discussions in the roundtable. The roundable was attented by representatives from farmers, startups, industry, academia and agricultural experts. Specific conclusions that emerged include the need for a platform to bring siloed initiatives, specially in the startup space, together so that collaboration is effected for scale and impact; the need for a national level AgriStack,i.e., a dynamic, public (with individual privacy protected) and open database of farm, farmer and crop grown, to spur innovation, further broad-base inclusion and enhance transparency in the subsidies, public finance and information aspects of Indian Agriculture. Our project, it emerged, in this sense, is timely and has the potential to contribute positively to the above goals and enhance farmer incomes.
Keywords: 330